Peranan Pendidikan Agama Islam pada Tradisi Berburu Babi (Maddengeng) Masyarakat Ponre Kabupaten Bone - Sultan Hasanuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Pig hunting tradition (maddengeng) is one of cultures in Ponre District, Bone Regency, South Sulawesi. It is done because pigs are declared as big pest that can cause agricultural and environmental damage. This study aims to describe the important role of Islamic Education on pig hunting tradition done by people of Ponre. This study used intrinsic and extrinsic approach. It employed qualitative descriptive method bydescribing the Islamic values from the observed culture. The data were collected by using some techniques including observation, interview, and documentation. In the case of data analysis, the gathered data were analyzed by using data reduction, data display, and drawing conclusion. The result shows that pig hunting tradition of Ponre people is divided into two activities, namely local pig hunting and massive pig hunting. Local pig hunting is usually done to identify the core of pest location by using simple utilities. Conversely, massive pig hunting is done by involving many people massively and using more complete utilities as well as systematic steps. In fact, in its realization, there aresome deviations done by Ponre people which against the Islamic law, such as doing some rituals that contain the elements of animism and dynamism before doing the process of pig hunting. Therefore, Islamic Education has an important role in straightening those deviate concepts by changing those rituals with praying together to Allah before doing pig hunting, and giving some understanding about how to properly clean things touched with pigs according to Islamic law.